Biocompatibility Test of Decellularized Cartilage Bovine Scaffold in Vitro and In Vivo - Achmad Fachrizal1, Dwikora Novembri Utomo1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Incidence of cartilage defects was reported at 65.00% of the routine arthroscopy procedures. Dr.Soetomo Teaching Hospital Network Bank developed a cartilage scaffold from bovine that has been deselularized decellularized cartilage bovine scaffold (DCBS). It takes a study of biocompatibility test to prove that DCBS is not cytotoxic to cells and not generate a host response. Objective: To analyze the biocompatibility of decellularized cartilage bovine scaffold (DCBS) in vivo and in vitro. Methods and Materials: The subjects were experimental rats and experimental with in vitro and in vivo trials. The subjects were treated by toxicity test with MTT assay, irritation test using Draize Scale, acute/ pyogenic systemic toxicity test by observing changes in body weight and temperature, and implantation test by observing fibrous capsule formation and Immunoglobulin G. Data was analyzed by using Kolmogorovsmirnov, Independent T-test, Mutivariate Analysis of Variance (MANOVA), and Mann Whitney. Result: The percentage of viable DCBS (81.78%) and CBS (92.45%) was ?70% of the control; thus, it is non-toxic to the cell. Draize scale in each group was in grade 0. Changes in body weight (p = 0.981) and temperature (p >0.05) had no significant association between groups. There was a significant difference mean of the fibrous capsule (p = 0.000) thickness and no significant difference in the mean number of Immunoglobulin G which was formed at week 1 (p = 0.87) and week 4 (p = 0.63) after implantation between CCBS and DCBS. Conclusion: The biocompatibility test shows that DCBS is compatible as a biomaterial.